Science and Technology for Sustainable Development (Bangladesh Journal of Scientific and Industrial Research, 2019)
This Special Issue contains the abstracts from the "Science and Technology for Sustainable Development" which was held on 12-14 December 2019 at the Bangladesh Council of Scientific and Industrial Research (BCSIR), Dr. Qudrat-I-Khuda Road, Dhanmondi, Dhaka-1205, Bangladesh. Organised by the Bangladesh Journal of Scientific and Industrial Research (BJSIR).Bangladesh J. Sci. Ind. Res. 54 (Special Issue), 1-134, 2019